Answer:
x = -11
Explanation:
It is convenient to use 3ยท4 = 12 as a common denominator. That is, we can clear the fractions by multiplying the equation by 12.
12(x +1)/2 -12(x +2)/3 = 12(x +3)/4
6x +6 -4x -8 = 3x +9 . . . . . . simplify
2x -2 = 3x +9 . . . . . . . . . . . . collect terms
-11 = x . . . . . . . . . . . . . . . . . . add -9-2x
_____
Check
(-11+1)/2 -(-11+2)/3 = (-11+3)/4 . . . . substitute -11 for x in the original
-10/2 - (-9/3) = -8/4 . . . . . . . . . . . . simplify
-5 +3 = -2 . . . . . . . . . . true